From dendritic mesoporous silica microspheres to waxberry-like hierarchical hollow carbon spheres: rational design of carbon host for lithium sulfur batteries. (7th September 2021) - Mu, Yanlu; Zhou, Tianyi; Zhang, Shuai; Li, Dexing; Jiang, Peng; Liu, Wen; Zhou, Henghui; Chen, Lan; Ge, Guanglu
Abstract: Fabricating sulfur host for the cathode with strong confinement effect and high dispersion of sulfur is vitally important to the development of high-performance lithium sulfur batteries. Benefiting from their unique and tunable structure, good conductivity and chemical inertness, hollow porous carbon materials has been considered as a promising candidate. Herein, precisely designed waxberry-like hierarchical hollow carbon spheres (h-CNS) have been synthesized as the sulfur micro-containers for lithium sulfur batteries. The prepared h-CNS/S electrode shows a good rate capability of 1311 mAh g −1 at 0.1 C and 962 mAh g −1 at 1 C. In addition, the h-CNS/S electrode also shows satisfactory long cycle performance with 622 mAh g −1 at 0.5 C and 400 mAh g −1 at 4 C over 600 cycles. The desirable performance can be attributed to the wedge-shape micro-containers which improve the high dispersion of sulfur inside the channels and inhibit the loss of intermediate polysulfide. Moreover, the unique structure can also enhance the transfer of both lithium ions and electrons which benefits to the rate capability of the lithium sulfur batteries.